2008
DOI: 10.1016/j.eurpsy.2008.01.1082
|View full text |Cite
|
Sign up to set email alerts
|

Reaction time in relation to the duration of heroin abuse

Abstract: Background and Aims:As a result of long-term heroin abuse we can see impairment of cerebral structures that leads to specific deficits in cognitive and conative area. Reaction time(RT) is an interval between reception of the certain stimulus and movement execution, as a response to received stimulus. It includes unharmed perceptive functions, attention, concentra- tion and psychomotor coordination. The aim of this study was to evaluate the effect of heroin abuse on RT.Method:90 heroin addicts, divided in tree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In the case of alcohol and other substance use disorders, studies have suggested that longer duration of alcohol use disorder (AUD), methamphetamine use disorder, and heroin use are correlated with more cognitive deficits. This is particularly true for response inhibition, reaction time, and cognitive flexibility (Laloyaux et al., 2012; Martinovic-Mitrovic et al., 2008; Monterosso, Aron, Cordova, Xu, & London, 2005). Moreover, research in AUD suggested that early onset of problems with alcohol is associated with stronger genetic susceptibility and poorer treatment outcome (Babor et al., 1992; Carpenter & Hasin, 2001; Cloninger, 1987; Schuckit et al., 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of alcohol and other substance use disorders, studies have suggested that longer duration of alcohol use disorder (AUD), methamphetamine use disorder, and heroin use are correlated with more cognitive deficits. This is particularly true for response inhibition, reaction time, and cognitive flexibility (Laloyaux et al., 2012; Martinovic-Mitrovic et al., 2008; Monterosso, Aron, Cordova, Xu, & London, 2005). Moreover, research in AUD suggested that early onset of problems with alcohol is associated with stronger genetic susceptibility and poorer treatment outcome (Babor et al., 1992; Carpenter & Hasin, 2001; Cloninger, 1987; Schuckit et al., 1995).…”
Section: Introductionmentioning
confidence: 99%